Antioxidant Effects of Methanol Extract of Allium cepa linn on Cyanide-induced Renal Toxicity in Male Wistar Rats (Nigerian Journal of Physiological Sciences, 2021)
Summary: The protective effects of onion was assessed in the Kidney of rats following sub-acute exposure to cyanide. These effects were compared to those of sodium thiosulphate (Na2S2O3), a classical antidote of cyanide toxicity. The rats were divided into 6 groups of 6 animals each. Group 1 was administered distilled water, Group 2,3,4, 5, and 6 were administered 600 mg onion/kg bwt/day, 7 mg KCN/kg bwt/day, 300 mg onion/kg bwt/day+ 7 mg KCN/kg bwt/day, 600 mg onion/kg bwt/day+ 7mgKCN/kg bwt/day, 600mg Na2S2O3/kg bwt/day+ 7mgKCN/kg bwt/day respectively for 2 weeks. Group 3, 4 and 5 were pre-administered with 300mg onion/kg bwt/day, 600mg onion/kg bwt/day and 600mg Na2S2O3 /kg bwt/day respectively for 2 weeks. Serum and urine creatinineand urea level were assessed as a measure of kidney function. Oxidative stress and antioxidant parameters were estimated in Kidney. Serum creatinine and urea levels were significantly higher in the cyanide treated rats compared with control. This was accompanied by significant reduction in the urine level of creatinine and urea. Co-administration with onion extract and Na2S2O3 reverse the situation in both the serum and urine. The level of malondialdehyde (MDA) in rats treated with cyanide (3.846±0.20μg/g) was significantly increased in the kidney relative to control (0.691±0.15μg/g). This was accompanied with a decreased in antioxidant enzymes Superoxide Dismutase (SOD) (2.0±0.09U/mg), Catalase (CAT) (0.014±0.001katf),Glutathione-S-Tranferase (GST) (0.015±0.009nMol/mg) and non-enzymatic antioxidant Reduced Glutathione (GSH) (4.006±0.09μg/ml) compared with control (4.8±0.13 U/mg, 0.047±0.001 katf, 0.022±0.0013 nMol/mg, 6.802±0.2 μg/ml respectively). Co-administration with onion extract and Na2S2O3 significantly increased these antioxidant enzymes and significantly decreased the concentration of malondialdehyde in the kidney. The results indicate that onion extract reduced lipid peroxidation in the kidney and increased antioxidant status of animals exposed to cyanide in a dose dependent manner